What mind does not know eyes cannot see!! – A case of bleomycin-induced flagellate hyperpigmentation - Janmenjoy Mondal,; Ananya Chandra,; Arunima Dhabal,; Kingshuk Chatterjee,; Arnab Kumar Ghosh, (Indian Journal of Case Reports, 2021)
Recognition of cutaneous side effects of bleomycin, a commonly used chemotherapeutic agent, is important to avoid unnecessary discontinuation of therapy. Here, we present the case of a 15-year-old boy who was undergoing treatment with standard BEP (bleomycin, etoposide, and cisplatin) regime, presented with flagellate hyperpigmented lesions in the back, arm, and thighs.